BELT AND ROAD INITIATIVE SEBAGAI GERBANG KONEKTIVITAS DI ASIA TENGGARA - Erba, Reyhan (Global and Policy Journal of International Relations, 2024)
This research aims to analyze the Belt and Road Initiative (BRI) as a connectivity gateway in Southeast Asia through a literature review method. The BRI, spearheaded by China, has become one of the largest global initiatives focused on infrastructure development and economic connectivity. This study reviews various literature including government reports, journal articles, books and other publications to evaluate the impact and implications of the BRI in the Southeast Asia region. The research results show that BRI has made a significant contribution to improving physical and economic connectivity between countries in Southeast Asia through infrastructure development such as roads, bridges, ports and trains. Apart from that, BRI also encourages increasing foreign direct investment and strengthening regional cooperation. However, this research also identified several challenges, including environmental sustainability issues, financial risks, and economic inequality between countries. In conclusion, although the BRI offers great opportunities for increased connectivity in Southeast Asia, a careful approach and risk mitigation strategies are needed to ensure long-term benefits for the entire region.Keywords: Belt and Road Initiative, BRI, Southeast Asia, Connectivity